The Use of Replica Media in Order to Improve Speaking Ability of 4-5 Yaer Old Children of TK ABA 02 Banjarejo - Annisa, Bhakti Nur; Tasuah, Neneng (Jurusan PGPAUD FIP UNNES, 2016)
The speaking ability on the fact of the matter is the skill to reproduce the current system of sound articulation to communicate the will, the needs and wishes, feelings in others. In children aged 4-5 years the speaking ability is used as a communication tool and understand the world, oral language proficiency in children will flourish because going by the maturation of the speech organs and functions, as well as environmental thinking helped develop it. One of the ways used to enhance the ability of talk in children through the selection of media made in attractive and fit the needs of the child. The purpose of this research is to know the difference in the ability to talk children aged 4-5 years before and after the use of the media the replica. This research uses experimental design pre-research of the design of one group pretest – posttest design. Sampling using a purposive sampling technique with class A TK ABA 02 Banjarejo as class experiments. Test hypotheses using a calculation of paired sample t-Test results obtained the value of the pretest and posttest retrieved value thitung with value 16,219 registration-sig (2-tailed) 0000 < 0.05 which means there is a significant difference between the value of the pretest and posttest. Obtained by mean of-21,433, the minus sign indicates that the average of the first group (pretest data). Then HO denied and Ha is received, this indicates that there is a difference in the average value of the pretest and posttest. Summary of the research is there is a significant difference in the level of ability to talk children aged 4-5 years after using media replicas. This means that the use of the media the replica in this research can enhance your speaking ability children aged 4-5 years.